A critical assessment of the relative success and failings of Central European countries to attract and sustain foreign direct investment - Gardner, Christopher (2006)
The purpose of this dissertation is to determine, firstly, what part foreign direct investment has played in the economic recovery of post-communist Central and Eastern European states in the last 15 years, and secondly, whether the countries in the region have successfully attracted and sustained this. The determinants of FDI for both transition countries and the investing companies are assessed, followed by specific case studies looking at where and how individual companies have invested, and why they have either remained in the market or moved production elsewhere. Before this can be done, though, an analysis of the situation in the countries in 1990 must be undertaken Ã¢ÂÂ only once this has been done can one understand the scale of the task the post-communist states faced.